Pengelolaan Paving Block Dari Limbah Plastik Ramah Lingkungan - Zulfikar Lating; Ira Deseilla Pawa; Ira Sandi Tunny (BADAN PENERBIT STIEPARI PRESS, 2024)
Reducing plastic waste is an urgent environmental issue and efforts are needed to educate students of SMA 1 Seram Barat about environmentally friendly waste management. This study aims to design an effective activity method to educate students of SMA 1 Seram Barat about the importance of reducing plastic waste. The proposed activity methods include counseling and presentations, group discussions, and field visits. Counseling and presentations will provide students with an initial understanding of plastic waste and its impact on the environment. Group discussions will provide an opportunity for students to share knowledge and ideas about plastic waste reduction. Field visits will provide first-hand experience about the process of processing plastic waste into Paving Blocks. The environmental awareness campaign will involve students in disseminating information about plastic waste reduction in schools and surrounding communities. Collaboration with external parties will provide broader insights into plastic waste reduction. The use of eco-friendly alternatives will encourage students to adopt lifestyle changes that reduce the use of single-use plastics. It is hoped that the implementation of this activity method will help students of SMA 1 Seram Barat to understand the importance of reducing plastic waste and have practical skills in environmentally friendly waste management. Through collaboration with external parties and involving the community, it is hoped that this plastic waste reduction effort can achieve a wider and sustainable impact.